Design and innovation for the Cultural Heritage. Phygital connections for a Heritage of proximity - Eleonora Lupo (Agathón)
The article presents reflections in the field of design for the Cultural Heritage within the ‘phygital’ scenario, in which the physical-analogical world converges and interacts with the virtual-digital world in a new fluid space. This condition has a significant impact on the cultural Heritage, both on its nature and definition and its accessibility and experience, as it becomes an indivisible continuum of tangible and intangible elements extended and connected in time and space. The potential of new technologies makes it possible to create significant connections between the Heritage, the users and the stakeholders, in a hybrid spatial dimension of both physical and metaphorical proximity. Design culture responds to these transformations (and to the need for new ways to relate to, become involved with and connect deeply with the Heritage, partly in response to the post-pandemic crisis) with an innovative approach to culture-driven technology. Defined as ‘culture-driven innovation’, it aims to innovate the user experience and hence the experience of designing with the Heritage, through the co-creation of augmented and amplified narratives, participatory and contributory co-curatorial practices, as well as performance practices and the creative re-use of the cultural Heritage.